Predicting Senior Secondary Schools Teachers' Social Intelligence by HEXACO-PI-R personality Traits based on Age Groups - Yahyazadeh-Jeloudar, Soleiman; Lotfi-Goodarzi, Fatemeh (International Journal of Asian Social Science, 2012)
The present study examined the relationship between social intelligence and personality traits among senior secondary schools teachers in Iran based on a selected demographic variable (age). In this research, 198 teachers were chosen using random sampling. They completed Tromsø Social Intelligence Scale (TSIS) and HEXACO- PI-R personality traits questionnaire. Data were analyzed using Pearson correlation coefficients by means of SPSS version17. The findings of the study showed that there were significant differences between teachers’ social intelligence and their age groups. Further, there were positive and significant relationships between teachers’ social intelligence and six personality traits (honesty-humility, emotionality, extraversion, agreeableness (versus anger), conscientiousness and openness to experience). Also multiple regressions show that the three personality traits (extroversion, conscientiousness and openness to experience) explain 0.40 variance of social intelligence. It was concluded that personality traits are factors that have a considerable role in people social intelligence.